Survival Rate Analysis of Early Stage Cervical Cancer Patients after Radical Hysterectomy in Ulin Banjarmasin General Hospital, Indonesia - Setyo Teguh; Hariadi Hariadi; Ferry Armanza; Hermin Sabaruddin (Berkala Kedokteran, 2021)
Abstract: Cervical cancer is a gynecologic disease that has a high level of malignancy and is a major cause of death from cancer in women. To be used as educational material for patients with cervical carcinoma when if there is known outcome of radical hysterectomy in patients with IB-IIA cervical carcinoma, it can be used as a basic data to know the success rate of radical hysterectomy.The sample was collected by consecutive sampling and we found a total of 55 IB-IIA cervical carcinoma patients who underwent a radical hysterectomy. The samples that met the inclusion criteria are 30 people. Data analysis using Chi-square/Fisher method (significant p-value <0.05).In this study, 16.7% of patients with cervical carcinoma from IB to IIA died in 3 years after radical hysterectomy was performed. The average age of patients with stage IB to IIA cervical carcinoma was 48.03 ± 12.21 years with ages ranging from 23 to 78 years. Stage IIA is 16 times more significantly at risk for mortality in cervical carcinoma patients than stage IB. The 3-year survival rate for patients with stage IB to IIA cervical carcinoma after radical hysterectomy was 83.3% with an average life span of 32.8 months. Patients with stage IB to IIA cervical carcinoma after radical hysterectomy have an average disease-free interval (DFI) of 33.0 ± 5.74 months. Keywords: Cervical Cancer, Radical Hysterectomy, Survival Rate